Pemanfaatan Teknologi Citra Satelit dan Drone untuk Pengelolaan Pertanahan di Wilayah Perbatasan Indonesia - Silalahi, Budi Jaya; Feryandi, Faus Tinus Handi; Sidabutar, Pandapotan (Sekolah Tinggi Pertanahan Nasional, 2021)
ABSTRACT Indonesia is an archipelagic state, which has border with other states on the land, sea, as well as on the air. In the sea, Indonesia has direct borders with ten countries, namely: India, Malaysia, Singapore, Thailand, Vietnam, Philippines, Republic of Palau, Australia, East Timor, and Papua New Guinea. As for the land, Indonesia has direct borders with three countries, namely Malaysia, Papua New Guinea and Timor Leste. As we know, Indonesian people who live in boundary zone are generally in poor conditions with lack of public services, such as: social, transportation and education service and facilities. However, the changing of government paradigm in the last two decades has prompted greater attention to this area. Recently, various government programs are driven to the border region, notably in provinces that have land borders, that is West Kalimantan, East Kalimantan, East Nusa Tenggara, and Papua Provinces. This paper will present about the land management programs in general which carried out in the Indonesia’s border area, for example in Entikong, Sanggau Regency, West Kalimantan Province, and Motaain, Belu Regency, East Nusa Tenggara Province. The main focus in this paper is the using of remote sensing and drones or unmanned aerial vehicle (UAV) data for supporting those programs. Furthermore, by promote the cooperation with other agencies and encourage community participation in the border zone, those programs can be succeeding in result. The conclusion of the study shows that the utilization of drones and imagery data is the key point of innovation in land management program in order to support the acceleration of sustainable development in the border region. Keywords: Border, Land Management, Drones (Unmanned Aerial Vehicle), Remote Sensing, Government Paradigms ABSTRAK Indonesia merupakan negara kepulauan yang berbatasan dengan negara lain baik di darat, laut, maupun di udara. Di laut, Indonesia berbatasan langsung dengan sepuluh negara yaitu: India, Malaysia, Singapura, Thailand, Vietnam, Filipina, Republik Palau, Australia, Timor Leste, dan Papua Nugini. Sedangkan untuk daratan, Indonesia berbatasan langsung dengan tiga negara yaitu Malaysia, Papua Nugini dan Timor Leste. Sebagaimana kita ketahui, masyarakat Indonesia yang tinggal di zona perbatasan umumnya berada dalam kondisi yang memprihatinkan dengan minimnya pelayanan publik, seperti: pelayanan dan fasilitas sosial, transportasi dan pendidikan. Namun, perubahan paradigma pemerintahan dalam dua dekade terakhir telah mendorong perhatian yang lebih besar pada bidang ini. Belakangan ini berbagai program pemerintah didorong ke wilayah perbatasan, terutama di provinsi yang memiliki perbatasan darat, yaitu Provinsi Kalimantan Barat, Kalimantan Timur, Nusa Tenggara Timur, dan Papua. Makalah ini akan memaparkan tentang kegiatan pertanahan secara umum yang dilakukan di wilayah perbatasan Indonesia, yakni di Entikong, Kabupaten Sanggau, Provinsi Kalimantan Barat, dan Motaain, Kabupaten Belu, Provinsi Nusa Tenggara Timur. Fokus utama dalam makalah ini adalah penggunaan data penginderaan jauh dan drone atau pesawat tak berawak (UAV). Lebih jauh, dengan meningkatkan kerjasama dengan instansi lain dan mendorong partisipasi masyarakat di zona perbatasan, kegiatan pertanahan tersebut dapat berhasil. Kesimpulan dari penelitian ini adalah pemanfaatan data drone dan citra merupakan kunci utama inovasi dalam aspek pertanahan guna mendukung percepatan pembangunan berkelanjutan di kawasan perbatasan. Kata kunci: Perbatasan, Pengelolaan Lahan, Drone (Pesawat Udara Tanpa Awak), Penginderaan Jauh, Paradigma